(untitled) (TAMADDUN NURI JURNALI, 2024)
This article contains an analysis the comprehensive reforms carried out in the healthcare sector, which is one of the branches of the social sphere in the Surkhandarya regio, also of some of the activities and changes carried out to restore the health of the population in the villages and strengthen the material and technical base of the medical sphere, and analyzes of information about these changes are also reflected.